Dr. Ana Torres — Deep Plane Facelift — Barcelona - Torres, Ana (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Ana Torres, practicing in Barcelona, Spain. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003352; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; spain; barcelona